2010
DOI: 10.1103/physreva.81.042330
|View full text |Cite
|
Sign up to set email alerts
|

Universal quantum computation using the discrete-time quantum walk

Abstract: A proof that continuous time quantum walks are universal for quantum computation, using unweighted graphs of low degree, has recently been presented by Childs [PRL 102 180501 (2009)]. We present a version based instead on the discrete time quantum walk. We show the discrete time quantum walk is able to implement the same universal gate set and thus both discrete and continuous time quantum walks are computational primitives. Additionally we give a set of components on which the discrete time quantum walk provi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
417
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 492 publications
(418 citation statements)
references
References 30 publications
1
417
0
Order By: Relevance
“…Their hallmark property is that on a regular lattice they spread quadratically more rapidly than random walks, i.e., ballistically rather than diffusively. This makes them valuable in quantum search algorithms [2] or even for general quantum computing [3]. Experiments on quantum walks range from realizations on trapped ions [4][5][6], to cold atoms in optical lattices [7][8][9], to light on an optical table [10][11][12][13][14][15], but there have been many other experimental proposals [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Their hallmark property is that on a regular lattice they spread quadratically more rapidly than random walks, i.e., ballistically rather than diffusively. This makes them valuable in quantum search algorithms [2] or even for general quantum computing [3]. Experiments on quantum walks range from realizations on trapped ions [4][5][6], to cold atoms in optical lattices [7][8][9], to light on an optical table [10][11][12][13][14][15], but there have been many other experimental proposals [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Lovett et al [33] later showed that the discrete time quantum walk can implement the universal quantum gate set, following Childs' [34] earlier proof of the equivalent result for the continuous time quantum walk. Ryan et al [35] experimentally demonstrated eight steps of a discrete time quantum walk over three points using an NMR-based quantum computer.…”
Section: Discrete Time Quantum Walksmentioning
confidence: 96%
“…They have been intensively investigated, especially in connection with quantum information science [3,4,5,6,7,8,9]. As in the classical case, QWs have been proposed as elements to design quantum algorithms [10,11,12,13] and more recently it has been shown that they can be used as a universal model for quantum computation [14,15].…”
Section: Introductionmentioning
confidence: 99%